The Red Queen in the Repository: metadata quality in an ever-changing environment (preprint of paper, presentation slides and dataset collection with validation schemas to IDCC2019 conference paper) - Philipson, Joakim (Stockholm University, 2019)
This fileset contains a preprint version of the conference paper (.pdf), presentation slides (as .pptx) and the dataset(s) and validation schema(s) for the IDCC 2019 (Melbourne) conference paper: The Red Queen in the Repository: metadata quality in an ever-changing environment. Datasets and schemas are  in .xml, .xsd , Excel (.xlsx) and .csv  (two files representing two different sheets in the .xslx -file). The validationSchemas.zip holds the additional validation schemas (.xsd), that were not found in the schemaLocations of the metadata xml-files to be validated. The schemas must all be placed in the same folder, and are to be used for validating the Dataverse dcterms records (with metadataDCT.xsd) and the Zenodo oai_datacite feeds respectively (schema.datacite.org_oai_oai-1.0_oai.xsd). In the latter case, a simpler way of doing it might be to replace the incorrect URL "http://schema.datacite.org/oai/oai-1.0/ oai_datacite.xsd" in the schemaLocation of these xml-files by the CORRECT:  schemaLocation="http://schema.datacite.org/oai/oai-1.0/ http://schema.datacite.org/oai/oai-1.0/oai.xsd"  as has been done already in the sample files here. The sample file folders testDVNcoll.zip (Dataverse), testFigColl.zip (Figshare) and testZenColl.zip (Zenodo) contain all the metadata files tested and validated that are registered in the spreadsheet with objectIDs.
In the case of Zenodo, one original file feed,
zen2018oai_datacite3orig-https%20_zenodo.org_oai2d%20verb=ListRecords%26metadata
Prefix=oai_datacite%26from=2018-11-29%26until=2018-11-30.xml ,
is also supplied to show what was necessary to change in order to perform validation as indicated in the paper.

For Dataverse, a corrected version of a file,
dvn2014ddi-27595Corr_https%20_dataverse.harvard.edu_api_datasets_export%20
exporter=ddi%26persistentId=doi%253A10.7910_DVN_27595Corr.xml ,
is also supplied in order to show the changes it would take to make the file validate without error.
Keywords: metadata, validation, research data, repositories, transformation; Computer and Information Sciences; Data- och informationsvetenskap (datateknik)